TANTANGAN DAN STRATEGI GURU DALAM MELAKSANAKAN BIMBINGAN DAN KONSELING DI SD NEGERI 2 MATA IE - Rahmat Iqbal; Sarifah, Intan; Kurniawati, Rizki; Alam, Faisal; Adawiyah, Radiatul (Universitas Negeri Semarang, 2025)
Guidance and Counseling (GC) in Elementary Schools plays a crucial role in supporting students' holistic development, encompassing academic, social, and emotional aspects. However, teachers still face various challenges in its practical implementation. This descriptive qualitative research aims to identify the specific challenges encountered by fifth-grade teachers at SD Negeri 2 Mata Ie in providing GC services, as well as the adaptive strategies they employ to overcome these obstacles. Through interviews and observations, the study found that the main challenges involve managing students with various behavioral and learning difficulties, such as slow learners, hyperactivity, or frequently disturbing peers. To address these issues, teachers developed innovative strategies, including participating in GC training, fostering close collaboration between teachers and parents, and integrating GC activities directly into daily lessons. These findings underscore the importance of enhancing teacher capacity and robust institutional support to ensure that GC services can function effectively at the elementary school level